Pola Komunikasi Orang Tua Dalam Meningkatkan Nilai Keberagamaan Generasi Muda Hindu Di Dusun Karang Anyar Lombok Barat - Ni Ketut Feriani; I Nyoman Wijana; I Nyoman Budhita (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2020)
The majority of the people in Karang Anyar Hamlet (almost 90%) are farmers. Due to full concentration in agricultural activities to fulfill the needs of the family's life, eventually taking up too much time, compared to the remaining time available to care for children. The education level of parents is relatively low, only graduating from elementary school, junior high school and some of high school education, but the young Hindu generation has high motivation in carrying out the teachings of Hinduism and Balinese culture inherited from their families, so it is necessary to examine the pattern of care for Hindu families toward their sons and daughters especially in enhancing religious values ​​in order to be able to create harmony in life between Hindus and other religious communities around it. Moreover, the interaction of young Hindu generation with other young people is still condusive. This research is entitled